Do It Yourself: Air Drag Force Experiment Using Paper and Scraper Sheet - Rizki Zakwandi; Ariswan Ariswan; Syifa Nurfalah; Tiana Azmi Alawiyah; Widiya Amanda; Ea Cahya Septia Mahen; Ade Yeti Nuryantini (STKIP Singkawang, 2021)
Free fall motion in air medium is only influenced by gravitation acceleration. However, there are several variables that caused the observations to be different with the concept. Variables, such as air drag and terminal velocity, are often teachers not presented in detail, causing misconceptions. This study aims to develop a simple experiment on free fall motion by identifying air drag and terminal velocity. The data in this study is the video of free fall motion of paper and scraper analyzed using Tracker video analyze. From the video analyzed, information is obtained in the form of time (t), track (l, θ), and velocity (v) of the object. This study shows that the air drag force increase unto the terminal velocity. The calculation of the drag coefficient giving the number of the paper 2,16 and the scraper 2,10. According to data analyzed, the air drag force is affected by the mass (m), area (A), and the air drag force (FD) with the linear correlation until it reaches the terminal velocity. The result of this study may use as references of free fall motion experiment with other objects and analyze.